2020
DOI: 10.5455/aim.2020.28.84-93
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Errors in Clinical Studies Published by Medical Journals of Ex-Yugoslav Countries

Abstract: Introduction: Certain methodological principles should be inexcusably followed when designing clinical or observational research to avoid bias and presentation of results that do not reflect the truth about the phenomenon that is the object of the study. Aim: The aim of this study was to compare the methodological quality of clinical trials and observational studies published in medical journals from ex-Yugoslav countries indexed in Pubmed/MEDLINE. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Number and percent of the evaluated studies that failed to meet each of the methodological criteria tested, number of the evaluated criteria not satisfied per database and number of studies that satisfied more than 4 criteria per database are presented in the Table 2 . References of the analyzed studies referred in both WoS and MEDLINE could be found in our previous publication ( 6 ), while the references of the studies covered only by WoS or only by Pubmed/MEDLINE ( 10 - 96 ) medical journals are given at the end of this article ( Table 3 and 4 ). When explanatory potential of journal impact factor, number of citations, time elapsed from publication and a database where a journal is referred were tested by linear regression in regard to the number of methodological criteria satisfied per study, the linear regression model was obtained by backward deletion method and achieved R2 adjusted of 0.166 (F=13.827, df1 = 2, df2 = 127, p=0.000).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Number and percent of the evaluated studies that failed to meet each of the methodological criteria tested, number of the evaluated criteria not satisfied per database and number of studies that satisfied more than 4 criteria per database are presented in the Table 2 . References of the analyzed studies referred in both WoS and MEDLINE could be found in our previous publication ( 6 ), while the references of the studies covered only by WoS or only by Pubmed/MEDLINE ( 10 - 96 ) medical journals are given at the end of this article ( Table 3 and 4 ). When explanatory potential of journal impact factor, number of citations, time elapsed from publication and a database where a journal is referred were tested by linear regression in regard to the number of methodological criteria satisfied per study, the linear regression model was obtained by backward deletion method and achieved R2 adjusted of 0.166 (F=13.827, df1 = 2, df2 = 127, p=0.000).…”
Section: Resultsmentioning
confidence: 99%
“…Scientometrics with its various indices is a reliable method for evaluation of scientific development ( 1 , 2 , 97 ). Name bibliometrics in the seventies was introduced to denote a quantitative study of the communication process using mathematical and statistical methods to books and other media of communication ( 6 ). More specifically, in 1969 was introduced the name scientometrics relating to scientific field that deals with the study of science as an information process by applying quantitative (statistical) method, and later Tibor Braun (founder of the International Journal of Scientometrics), introduced the name Scientometrics ( 97 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two main reasons why the authors are not publishing in their native language at international medical journals. The first is obvious, number of international medical journals published in national language is small and decreasing from year to year; many coutries do not have any more international medical journals published in national language [9]. The second reason is also important, but less clear: the authors themselves may avoid publishing at journals printed in national language because they fear that their work will pass unnoticed by wider scientific community which does not understand this native language [10].…”
Section: Discussionmentioning
confidence: 99%